A note on the uniqueness of solutions to rational expectations models - Christopher Heiberger; Torben Klarl; Alfred Maußner (Universität Augsburg, Institut für Volkswirtschaftslehre, 2012)
Klein (2000) advocates the use of the Schur decomposition of a matrix pencil to solve linear rational expectations (RE) models. Meanwhile his algorithm has become a center piece in several computer codes that provide approximate solutions to (non-linear) dynamic stochastic general equilibrium (DSGE) models. A subtlety not resolved by Klein is whether or not a certain Schur decompostion could fail to solve the model while a second one would provide a solution. We show that this cannot happen.
urn:nbn:de:bvb:384-opus4-710991
Keywords: C63; C88; E37; 330; Linear Rational Expectations Models; Schur Decomposition; DSGE Models